Lessons from the financial crisis - Smaga, Paweł (Journal of Public Governance, 2014)
The aim of this paper is to identify challenges faced by the financial safety net and to verify whether, as a result of the financial crisis, there is a significant paradigm shift of financial stability. To do so, the author uses a comparative method and literature review. The paper presents changes in the financial system, financial stability, regulation and supervision before and after the crisis. One can observe a dynamic increase in the size of the financial system, the emergence of SIFIs, excessive leverage, and the rise of shadow banking. The importance of financial stability increased as an objective of economic policy (introduction of macroprudential policy). In regulation and supervision, there are important attempts to bridge the gaps and to strengthen the role of central banks in safeguarding financial stability.